Perancangan Game Platformer 2D “Seasonal” Pada Web - Aprilia, Silvana; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
“Seasonal” is a 2D game with platformer and single player genres. This game can be played on the web or devices that can access the browser. Game is developed using Unity 2019.4.14f1. Players are required to collect 4 treasure boxes from 4 seasons. Those seasons are Spring, Summer, Autumn and Winter. Testing is done by blackbox testing, alpha testing and beta testing. Alpha testing is tested by the supervisor while beta testing is tested by 48 respondents. The results of beta testing show that "Seasonal" is a game that can be enjoyed by all groups from teenagers to adults. “Seasonal” also playable on Google Chrome, Microsoft Edge, Safari, and Opera browsers. In addition, "Seasonal" has interesting gameplay but has level of difficulty between normal to difficult.